Homofobia e heterossexismo na escola: um estudo sobre significações de professores gays que atuam na educação básica - Toledo, Rodrigo (2018)
The purpose of this research is to understand the concepts constructed by teachers who are gay about the multiple violence and prejudices experienced in relation to their sexual orientation and their expression approach types. To enable to comply with this, we seek to understand the historical constitution of heterosexism and homophobia in the Brazilian society. We have focused on studies that recall the trajectory of LGBTT movement and the various forms of expression of homophobia, focusing especially on their expressions in school. We also have reflected on the school as a powerful space for confronting homophobia and how this institution can eventually also become a space for violence Finally, the study also focused on understanding struggling strategies and homophobia conflict. Hence, four sessions of conversation were held with teachers who identified themselves as gays and who work in the basic education. The selection of the teachers who participated of the r4esearched was based on the "snowball" strategy, according to May's proposition, in which the first participant selected, which met the profile defined for the study (being a teacher who defined him/herself gay in public schools of basic education indicated a new entrant and so on. The analysis was done by Núcleos of Significação (Meaning Concept Cell). The research concluded that prejudice and discrimination against the LGBTT population, in most cases, result in situations in which these people are humiliated and / or beaten, initially because their expression of gender / sexuality is considered to be outside of the patterns of heteronormativity. This fact suggests that it is fundamental to face conservatism, which is expressed in practices that accentuate prejudice and violence addressed to the LGBTT population in the school environment. In this sense, when the school does not define itself politically against homophobic violence, it can become a space for the production of violence and a reaffirmation of the exclusions experienced by the school actors. We have realized that the daily school life has not been conducive for teachers who wish to have a practice committed to the transformation of reality to achieve it, especially when they are engaged in a work involving education related to gender relations and the fight against homophobia. We have concluded that the participants of this research as they were classified themselves as "good students" and having faced violence in the school during their initial school time and then as teachers, had to create tools and strategies by themselves to face the challenges presented by the their gender condition. It is important to emphasize that to overcome the difficulties experienced by the participants was only possible in the adult life and that they survived in school through the establishment of partnerships and supports (personal and institutional). Considering this scenario, such partnerships and supports were fundamental to the participants to remain in school as teachers, developing their work in a positive way. Thus, the results of this study suggest that it is essential that schools develop projects, together with social movements, to devote themselves to understand, discuss and accept differences in sexual orientation, so that these actions imply that students dropping out of school out by fear and / or discrimination, and building professional settings in which gay teachers also remain in school without violence